Why is the mathematics educator called inspiring? - Simamora, Rustam Effendy; Darmayasa, Jero Budi; Kamara, Jean Gloria (Journal of Honai Math, 2022)
Inspiration plays a significant role in sparking or enhancing the learning motivation of prospective mathematics teachers (PMTs). InspirationÂ will alsoÂ influenceÂ the mathematical identity of PMTsâ€™ when they become professional mathematics teachers. AÂ mathematics teacher educator (MTE) can be a source of inspiration for PMTs; hence, a study must identify and explain why an MTE is considered inspiring. This study attempts to develop the theory of inspiring MTEs profiles based on the experience of PMTs. This study included 21 students and 7 lecturers of the Mathematics Education Department in a public university in Indonesia. This qualitative research was conducted employing a grounded theory constructivist approach. The findings revealed that inspiring MTEs possessed the following characteristics: â€œcreating a sense of comfort, being knowledgeable, being motivating, providing fun and enjoyable learning, imparting new insights and comprehension, and being disciplined and authoritative.â€ According to this theory, an inspiring MTE creates a sense of comfort through their gracious, friendly, humble, and humorous personality. Fun and enjoyable learning in this study is learning that provide a sense of comfort, fun learning, interactive learning, and carrying out evaluations. MTEs give new insight and understanding by explaining in detail, systematically, and easily understood, sharing creative ideas, and providing scaffolding. Implications of this finding are discussed.